Failure to clear intra-monocyte HIV infection linked to persistent neuropsychological testing impairment after first-line combined antiretroviral therapy - Shiramizu, B. (2011)
HIV-associated neurocognitive disorders (HAND) persist despite plasma HIV RNA suppression with antiretrovirals (ARV). Sequestered reservoirs in the central nervous system and circulating monocytes are theorized to contribute to persistent brain injury. We previously demonstrated that elevated intracellular HIV DNA from circulating cells was associated with HAND in ARV-treated and ARV-naive subjects. We now report that failure to suppress intra-monocyte HIV DNA 3.5 years after initiating ARV is linked to persistent HAND and subjects with dementia are least likely to suppress intra-monocyte HIV DNA at 3.5 years. These findings suggest that antiviral strategies may need to target intra-monocyte HIV DNA.